Modelling associated factors of maternal age at first birth in Ethiopia: Gamma regression approach - Adimias Wendimagegn Agegnehu; Butte Gotu Arero (PLoS ONE, 2026)
Background Maternal age at first birth (AFB) is a key indicator of reproductive health, influencing maternal and child outcomes, population dynamics, and socio-economic well-being. Early childbearing increases risks of maternal morbidity, poor neonatal outcomes, and intergenerational poverty. Despite progress in Ethiopia, disparities in AFB persist across regions, religions, and residential settings, particularly among women who have already given birth. This study determines the magnitude and direction of effects from religious, regional and residential determinants of maternal AFB in Ethiopia. Methods Data were drawn from 5,839 women included in the 2019 Ethiopia Mini Demographic and Health Survey (Mini EDHS 2019). A comparative modeling framework was employed; fitting Generalized Linear Models (GLM), Generalized Linear Mixed Models (GLMM), and distributional Gamma regression models to examine the consistency of the coefficients for covariates across different modeling framework. Both classical estimation (Maximum Likelihood Estimation) and Bayesian inference via Markov Chain Monte Carlo (MCMC) were used. Results Among women in Ethiopia who had experienced a first birth by the time of the survey, the average maternal age at first birth was 18.7 years(95% CI: [18.2, 19.3]), indicating that a substantial proportion of women begin childbearing at the lower limit recommended by the World Health Organization. Regional differences in mean maternal age at first birth were notable: women in Amhara (4%), Oromia (3%), SNNPR (3%), Benishangul-Gumuz (3%), and Gambela (8%) had earlier average maternal age at first births, whereas those in Addis Ababa (11%), Somali (4%), and Dire Dawa (4%) delayed childbirth compared to Togray. Variability in AFB also differed by region, with higher dispersion observed in Afar (37.7%), Benishangul-Gumuz (37.7%), Somali (36%), Gambela (32.3%), SNNPR (27.1%), and Harari (25.9%), while Addis Ababa (22.1%) and Dire Dawa (13.1%) showed lower variability. Women who have already given birth and identify as Orthodox or Protestant tend to experience a higher average age at first birth, with increases of approximately 4% and 3%, respectively, relative to Muslim women. Conversely, women classified under the “other religions” category tend to have their first child approximately 5% earlier than Muslim women. Residence influenced both mean and variability: rural women who had already given birth experienced first births about 5% earlier than urban women and exhibited 7.3% greater dispersion, indicating more heterogeneous reproductive patterns. Conclusion Maternal age at first birth in Ethiopia remains low (18.7 years), with significant disparities in mean and variabilities across religion, residence, and region. Women from rural areas, Muslim backgrounds, and regions such as Amhara, Oromia, Benishangul-Gumuz, SNNPR, and Gambela are more likely to give birth earlier, while urban women, particularly in Addis Ababa, Dire-Dawa, and Somali, tend to delay childbearing. The persistence of very early childbearing (as young as 10 years) highlights urgent reproductive health challenges. These findings call for context-specific policies: expanding girls’ education, delaying marriage, and strengthening youth-friendly reproductive health services in rural and high-risk regions; engaging religious leaders and institutions as partners in promoting delayed childbearing; and addressing structural inequities through regionally tailored programs that respect cultural and pastoralist lifestyles.